A hyaluronic acid-derived imaging probe for enhanced imaging and accurate staging of liver fibrosis. (1st November 2022) - Wang, Xiaoming; Zhang, Xiaoqin; Li, Zhiqian; Xiao, Xueyang; Guo, Shiwei; Pan, Dayi; Zhang, Hu; Tian, Xiaohe; Gong, Qiyong; Gu, Zhongwei; Ma, Xuelei; Luo, Kui
Abstract: Timely detection and accurate staging of liver fibrosis still remains a challenge. Herein, we report a hyaluronic acid (HA)-based magnetic resonance (MR)/fluorescence imaging agent, HA-Target-Cy5.5-DOTA-Gd (HTCDGd) with oxyamine groups to target allysine in the fibrous tissue, and a control agent, HA-Cy5.5-DOTA-Gd (HCDGd) without the targeting group was also prepared. Both agents have a nanoscale size with a high relaxivity, and show a rapid blood clearance rate and great biosafety. Compared to HCDGd, interaction of the targeting oxyamine groups in HTCDGd with allysine of collagen in the fibrosis tissue facilitates high accumulation of HTCDGd in the liver and allows sensitive and long-term detection of liver fibrosis at the early stage (Ishak = 3) and the late stage (Ishak = 5) in animal models via its enhanced MR signal. Those results are confirmed by fluorescence images. Overall, HTCDGd has been demonstrated as an effective agent for non-invasive and accurate diagnosis of liver fibrosis. Graphical abstract: Unlabelled Image